Arterial anomalies of the celiac trunk and median arcuate ligament compression in dogs and cats assessed by computed tomography angiography. Issue 2 (2nd November 2017) - Le Pommellet, Hélène M.; Scansen, Brian A.; Mathys, Dimitria A.; Mollenkopf, Dixie F.; Reeves, Lauren; Skinas, Melissa L.; Patel, Mira
Abstract: Objective: To identify abnormalities of the celiac artery (CA) and major branches in dogs and cats by computed tomography angiography (CTA). Study design: Multi‐institutional retrospective case series. Animals: Two hundred fifty‐four dogs and 13 cats. Methods: Abdominal CTA images from 2009 to 2017 were reviewed. Logistic regression models were used to evaluate the relationship between CA abnormalities and sex, age, size of dog, concurrent venous anomaly, or presence of gastrointestinal signs. Results: Abnormalities in the CA were observed in 32 animals (11.9%) including 9 with abnormal branching (3.4%) and 23 with CA compression (8.6%). A celiacomesenteric trunk was observed in 8 (2.9%; 6 dogs, 2 cats). The splenic artery originated from the cranial mesenteric artery in 1 dog; the hepatic arterial branches originated from the left gastric artery in another. Four out of 32 animals (12.5%) with an arterial anomaly had another vascular abnormality. Large breed dogs were more likely to have an arterial anomaly (OR 4.3, 95% CI: 1.18‐15.5, P  = .02) and 12 times more likely to have CA compression (OR 12.0, 95% CI: 1.4‐97.7, P  = .02) compared to small breed dogs. Dogs with CA compression were more likely to present for gastrointestinal signs (OR 3.6, 95% CI: 1.2‐10.3, P  = .01). Conclusion: Anomalies of the celiac trunk are apparent on CTA and may impact surgical or image‐guided intervention. Compression at the origin of the CA was apparent on imaging, similar to the median arcuate ligament syndrome in people, although the significance of this finding in dogs is unknown.